2020
DOI: 10.31088/cem2020.9.4.12-23
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological and immunohistochemical features of lymph nodes in COVID-19 patients (autopsy study)

Abstract: Introduction. The pathogenesis of the novel coronavirus infection COVID-19 is being actively studied. Nevertheless, our up-to-date knowledge of lymphoid tissue response in the secondary immune organs dur-ing severe COVID-19 remains extremely limited. The aim of the study was to evaluate patterns of immu-nomorphological alterations in lymph nodes in patients with severe COVID-19 and to assess lymphocytes functional activity in them. Materials and methods. Lymph node tissue (autopsy material) from 17 deceased pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Tubular necrosis and renal infarctions, associated with septic conditions, were seen in 2 cases in our study. Splenic enlargement due to sepsis, major follicular reduction, lymphatic infiltration, necrosis and [45]. The paracortical zone showed a significant reactive plasmocytosis with T-helper existence-a morphologic substrate of humoral immunity, which may testify a noneffective humoral response in COVID-19-effected patients with simultaneous T-cell immunity failure.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Tubular necrosis and renal infarctions, associated with septic conditions, were seen in 2 cases in our study. Splenic enlargement due to sepsis, major follicular reduction, lymphatic infiltration, necrosis and [45]. The paracortical zone showed a significant reactive plasmocytosis with T-helper existence-a morphologic substrate of humoral immunity, which may testify a noneffective humoral response in COVID-19-effected patients with simultaneous T-cell immunity failure.…”
Section: Discussionmentioning
confidence: 94%
“…An immunohistochemical study revealed the predominance of CD4 + T-helpers in the paracortical zone, depletion of cytotoxic CD8 + lymphocytes, an increase in the number of both lymphocytes expressing the PD-1 suppressor protein and activated lymphocytes expressing the CD30 activation antigen. CD123-positive plasmacytoid dendritic cells secreting type 1 interferon were found in a significant amount in the lumen of the sinuses and in the paracortical zone [45].…”
Section: Discussionmentioning
confidence: 98%
“…Cardiac complications caused by infection with SARS-CoV-2 are deemed to be associated with both direct and indirect viral effects on the myocardium. The direct mechanism of myocardial injury is promoted by a viral invasion of cardiomyocytes via the viral S-protein, a type of transmembrane glycoprotein, and the interaction of the virus with angiotensinconverting enzyme (ACE) 2 present in cardiac cells [41][42][43]. However, the viral entry into cardiomyocytes depends not only on the viral S protein binding to the host-cell receptors.…”
Section: Discussionmentioning
confidence: 99%